“What do experts say?” Visual complexity and community acceptance of Pua Kumbu / Wan Juliana Emeih Wahed, Saiful Bahari Mohd Yusoff and Noorhayati Saad - Emeih Wahed, Wan Juliana; Mohd Yusoff, Saiful Bahari; Saad, Noorhayati (UiTM Perak Press, 2022)
This chapter highlights the aesthetic perceptions of academicians regarding the complexity of Pua Kumbu design motifs and the community acceptance of this tangible heritage. The complexity of the symbols presented in the design motifs contributes to the current lack of interest in this art form, especially among the young generation, tourists and other races in Sarawak. The complexity of the symbols has also led to these motifs being further misunderstood, as well as the mistreatment and misuse of this majestic art form. Therefore, this research used a qualitative approach to explore the perspectives of four academicians in the fields of textiles, art and culture. In-depth interviews with semi-structured questions were conducted, as was observation and analysis of the relevant documents. According to the findings, weavers are the masterminds behind the visual complexity of Pua Kumbu, which reveal Iban knowledge through the design motifs. In conclusion, prior knowledge of Iban culture can broaden the community acceptance of this art form, minimise the knowledge gap and prevent these masterpieces from being forgotten and neglected.